2022
DOI: 10.1007/s11427-022-2173-9
|View full text |Cite
|
Sign up to set email alerts
|

Loop CD20/CD19 CAR-T cells eradicate B-cell malignancies efficiently

Abstract: CD19 chimeric antigen receptor (CAR) T cells have shown robust efficacy in relapsed and refractory acute lymphoblastic leukemia (R/R ALL), but compromising result in chronic lymphoblastic leukemia (CLL) and non-Hodgkin's lymphoma (NHL). CD19− relapse and the lack of CAR-T cell persistence which result in treatment failure are considerable obstacles to overcome.CAR-T targeting CD20 is an option for salvaging CD19 CAR-T failure. Previous studies have established variant structures of bispecific CAR-T which could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…After that, castor oil (CO, 4.7 g, 1 eqv) was added and stirred at 70°C for another 3 h. Finally, –NCO peak was fully disappeared at 2270 cm −1 (Figure 2a (black line)). The –NH stretching vibrations of the urethane group ranges from 3230 to 3380 cm −1 indicates the polyurethane (Figure 2a (black line)) 19 . However, –C=O stretching vibrations 1670–1750 cm −1 was overlapped between urethane (–OC(=O)–NH–) and ester (–C(=O)–O–) functionalities.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…After that, castor oil (CO, 4.7 g, 1 eqv) was added and stirred at 70°C for another 3 h. Finally, –NCO peak was fully disappeared at 2270 cm −1 (Figure 2a (black line)). The –NH stretching vibrations of the urethane group ranges from 3230 to 3380 cm −1 indicates the polyurethane (Figure 2a (black line)) 19 . However, –C=O stretching vibrations 1670–1750 cm −1 was overlapped between urethane (–OC(=O)–NH–) and ester (–C(=O)–O–) functionalities.…”
Section: Resultsmentioning
confidence: 98%
“…A mixture of PCL‐diol (10.1 g, 1 eqv), TDI (1.45 mL, 2 eqv), and DBTDL (1 mol%) were heated at 70°C for 1 h (Table 1, entry 1 (first step)). The decrement of the –NCO peak at 2270 cm −1 and –OH peak at 3596 cm −1 (Figure 2a (green line)) indicates the condensation of –OH and –NCO functionality and the generation of prepolymer 19 . After that, castor oil (CO, 4.7 g, 1 eqv) was added and stirred at 70°C for another 3 h. Finally, –NCO peak was fully disappeared at 2270 cm −1 (Figure 2a (black line)).…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the effect of vIL7FL on DC populations in the tumor-bearing hemisphere. In the steady-state mouse brain, subcutaneous Flt3L delivery has been shown to increase antigenpresenting cDC populations (82). Additionally, these cDCs arose from the differentiation of pre-DC progenitors that had migrated into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional CAR-T cells, CAR-CAT cells had a lower oxidation state with less ROS accumulation in both basal and activated states, while maintained stronger anti-tumor activity even at high H 2 O 2 levels. These results showed that protecting CAR-T cells from exhaustion mediated by tumor-associated oxidative stress could significantly improve their efficacy (82). To date, ICB targeting PD-1 and programmed cell death ligand 1 (PD-L1) have achieved clinical success for solid tumors (83).…”
Section: Tme Leads To Premature Exhaustion Of Car-t Cellsmentioning
confidence: 99%
“…Our previous study demonstrated that scFv function can be influenced by the type of linker used and the order of the heavy and light chain, even with the same nucleotide sequences [ 31 ]. Therefore, several linkers and different arrangements of CD3VL/CD3VL/CD19VL/CD19VH were evaluated to optimize the functionality of the dual-antibody in this study, while we only present the structures in which DuAb and EDuAb exhibit the best capacity in eliminating tumor cells.…”
Section: Discussionmentioning
confidence: 99%